The image of the teacher in Ivan Vazov’s works: between the englightenment cult and positivism - Чавдарова, Дечка (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The subject of the present analysis is the conceptualisation of the figure of the teacher in Ivan Vazov’s works. Evoking the epoch of Bulgarian National Revival and the 19th-century struggle against the Ottoman yoke, his books convey the idea of the teacher’s high mission as people’s enlightener, show the transformation of the teacher into a revolutionary, but also give examples of injustice suffered by the teacher from public authorities. In the paper, particular attention is paid to the image of the teacher in Vazov’s novel ʻKazalarskaya tsaritsaʼ (ʻThe Empress of Kazalarʼ), where the utilitarian idea of modest, persistent teaching work for the cultural development of the people blends with elements of utopian discourse. On the basis of these observations a conclusion is formulated about Vazov’s role in constructing the concept of the teacher in Bulgarian culture.